Empowering Female Teachers through Health Literacy, Reproductive Health and Lifestyle Modifications in Osun State, Nigeria - Uchechukwu Charles Osu; Olajumoke Oyetola Adegbite; Taiwo Oluwaseyifunmi Olunubi; Foyinsola Genevieve Ogunniyan; Patricia Ifeoma Afolabi (Journal of Arts, Humanities and Social Science)
The study investigated nexus among health literacy, reproductive health and lifestyle modifications among women of reproductive age in teaching profession in Osun State, Nigeria. Purposive and simple random sampling techniques were employed to selected one-hundred and eighty-six teachers. A self-designed instrument was used to elicit information from the participants. Both descriptive and inferential statistical tools were explored to analyse the generated data. The findings of the research demonstrated a moderate positive association between health literacy and reproductive health of women of reproductive age in teaching profession. The study further revealed a significant relationship between lifestyle modifications and reproductive health among women of reproductive age in the teaching profession. The findings indicated that the top strategies included simplifying health information using plain language,  providing training for healthcare providers, and using visual aids like diagrams, pictures, and videos. Other notable strategies included offering reproductive health services and counselling, providing access to accurate information, and promoting physical activity, healthy eating habits, stress management, and healthy sleep habits. The study concluded that health literacy, reproductive health and lifestyle modifications of women of reproductive age go a long way in enhancing their well-being and overall effectiveness in teaching profession. Policymakers and health educators should promote and support lifestyle modification programs that empower women teachers to make informed choices about their reproductive health.